Understanding National Christianities in the Nordic Region: A History About "Continuity or Rupture" and "Inclusion or Exclusion" - Claesson, Urban (A journal of church and state, 2025)
This article summarizes the results of the special issue and its focus on the complex relationship between Christianity and nation building in the Nordic region. By examining the other articles, this concluding contribution, on the one hand, argues that Christianity has played a dual role in both integrating and excluding various groups within Nordic societies—the opposing concepts of "inclusion or exclusion" have been employed here. On the other hand, the article also employs the contrasting concepts of "continuity or rupture" in critique of the general secularization paradigm that implies a break between a former era of religion and a modern era of secularity in order to highlight the evolving and continuous role of religion from the mid-nineteenth century to the early twenty-first century.Key contributions from the special issue include analyses of how Christian values influenced democratic citizenship projects in Finland and Sweden, the mobilization of Lutheran faith against Nazi occupation in Norway, and the role of Christianity in shaping national identity during the interwar period. The issue also addresses the exclusionary aspects of religion, such as anti-Semitism in nineteenth-century Finland and the use of Christian identity to marginalize Muslims in contemporary Sweden.This concluding article also highlights the interdisciplinary collaboration within the Historical Study of National Christianities network and its focus on the complex and multifaceted role of religion in Nordic history.